2020
DOI: 10.3390/su12031132
|View full text |Cite
|
Sign up to set email alerts
|

Biodeterioration Patterns and Their Interpretation for Potential Applications to Stone Conservation: A Hypothesis from Allelopathic Inhibitory Effects of Lichens on the Caestia Pyramid (Rome)

Abstract: The colonisation of stone by different organisms often leaves biodeterioration patterns (BPs) on the surfaces even if their presence is no longer detectable. Peculiar weathering patterns on monuments and rocks, such as pitting phenomena, were recognised as a source of information on past colonisers and environmental conditions. The evident inhibition areas for new bio-patinas observed on the marble blocks of the Caestia Pyramid in Rome, recognisable as tracks of previous colonisations, seem a source for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Mortar porosity allows the penetration of water and soluble salts coming from the masonry materials themselves [70] and the external adjacent embankments, increasing the susceptibility of the stone surface and creating good indoor conditions for the establishment and development of microbial biofilms. Results showed that the samples collected from the internal walls of our study site included a wide range of microorganisms found in environments characterized by almost constant temperatures throughout the year and quite high humidity levels, such as caves [71], hypogea [72], and grottoes [73]. In order to provide information on the diversity of biofilm microorganisms, the combination of molecular techniques with culture-dependent methods has been used for the first time in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Mortar porosity allows the penetration of water and soluble salts coming from the masonry materials themselves [70] and the external adjacent embankments, increasing the susceptibility of the stone surface and creating good indoor conditions for the establishment and development of microbial biofilms. Results showed that the samples collected from the internal walls of our study site included a wide range of microorganisms found in environments characterized by almost constant temperatures throughout the year and quite high humidity levels, such as caves [71], hypogea [72], and grottoes [73]. In order to provide information on the diversity of biofilm microorganisms, the combination of molecular techniques with culture-dependent methods has been used for the first time in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The control of fungi in cultural heritage assets is an important issue which was investigated using various ways to limit their development and growth such as the use of natural substances employed as green conservation strategies and the utilization of engineered nanomaterials [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…(e.g., Caloplaca chalybaea) was an unknown taxon of Trebouxia, typical of the Mediterranean area. These three lichens (among others) identified in the City Hall were also found on natural limestone outcrops, buildings and monuments [58][59][60][61][62]. ON479853 Fungi * Lichens are taxonomically classified by their fungal partner, so all lichens belong to the Fungi kingdom.…”
Section: Organisms On the Cross Of The Inquisition Limestonementioning
confidence: 99%